The Impact of Globalization on Curriculum Development in Higher Education - Somchai Jindarat; Narongchai Chaiyawat (Program Studi DIII Rekam Medis dan Informasi Kesehatan, 2023)
This study examines the influence of globalization on curriculum development in higher education institutions. By analyzing how universities worldwide adapt their curricula to meet the demands of an interconnected global economy, the research highlights the integration of international perspectives, global issues, and multilingual competencies. Findings suggest that curricula incorporating global challenges and diverse viewpoints better prepare students for the complexities of the modern workforce.